Draft Genome Sequence of Cyclic Lipopeptide Producer Pseudomonas sp. Strain SWRI103, Isolated from Wheat Rhizosphere - Zarvandi, Samira (Microbiol Resour Announc, 2020)
The draft genome sequence of wheat rhizosphere isolate Pseudomonas sp. strain SWRI103 is reported. This strain carries several gene clusters encoding nonribosomal peptide synthetases (NRPSs), including a system for cyclic lipopeptide (CLP) production, and genes for carotenoid biosynthesis.